Carrying On the Tradition: A Social and Intellectual History of Hadith Transmission Across a Thousand Years - Davidson, Garrett. (Islamic History and Civilization, 2019)
In Carrying on the Tradition Garrett Davidson employs a variety of largely unutilized print, as well as archival sources collected from the Near East, North Africa, India, Europe, and North America. He analyses these sources to excavate the fundamental reinvention of the conceptions and practices of hadith transmission that resulted from the establishment of the hadith canon. Further, the book examines how hadith scholars reimagined the transmission of hadith, not as a scholarly tool, as it had originally been, but instead as, among other things, an act of pious emulation of the forefathers. It demonstrates the emergence of new genres and subgenres of hadith literature, as a result of this shift, examining them as artefacts of the cultural, social, and intellectual history of Muslim religiosity from the tenth to twentieth centuries.